Development of Shoulder and Wrist Test Instruments Based on Digital - Mesnan Mesnan; Amir Supriadi (UNIB Press, 2022)
A test tool and measurement of shoulder flexibility and developed to be a sports lecturer's guide in teaching courses test and measurement. This research was developed by adapting the Borg & Gall educational research and development model. The development procedure used includes several stages: 1) recognizing the content of the product being developed, 2) developing the initial game product, 3) expert validation, 4) testing field The data analysis technique used in this research is done in two ways, namely quantitative and qualitative. The subjects of this study were students of the sport science faculty in the test and measurement subject. The resulting product has been evaluated by experts, tested and revised and validated by media, material and practitioner experts through a questionnaire consisting of various questions. effectiveness of the product development of digital-based shoulder & wrist test kits has the results of 85% material experts, 96% media experts and 85% by practitioners. The results of field trials show a value of 90% with a very feasible category so that it can be used for use. Thus, it can be stated that the development of digital-based shoulder & wrist test kits is effectively used as the basis for developing science and technology in the field of sports.